Legal Issues in Dealing with Staff: A Study in Selected Hotels in Malaysia - Sharija Che Shaari; Jennifer Chan Kim Lian; Jakaria Dasan (2018)
The tourism industry is becoming one of the major contributors to Malaysia’s economy. It is evidenced by the Malaysia Tourism Transformation Plan (MTPP) which aims for the industry to generate annual revenue up to RM150 billion by 2020, compared to RM56.5 billion in 2010. In keeping up with the pace of development that this industry is experiencing, Malaysia is going through healthy growth in hotel openings. Thus, more employees are needed in the hotels. It is the objective of this study to investigate the legal issues faced by the hotels and its workforce. This socio-legal study used qualitative method. The primary data comprises of questionnaire and interview method undertaken to collect the data. This study adopted indepth, open ended interviews to determine the legal issues. The interviews were recorded, transcribed and categorized based on interview questions. The thematic analysis was employed to identify relevant themes after examination of the data. Based on the in-depth interview held with representatives from the hotel’s associations, hotel managements and the staff, it is interesting to note that these major issues have emerged, namely pertaining to terms and conditions of employment especially on non-compliance of terms and conditions, discrimination, safety and health, disciplinary, and sexual harassment. In conclusion, these findings are useful to those in hospitality industry as the hospitality industry plays major role in supporting Malaysia’s tourism industry. Thus, the industry players must address these legal issues so as to create harmonious relations between the management and workforce that will eventually lead to the survival and sustainability of the respective hotel. It will also ensure that the aim of MTPP is achieved.